The effectiveness comparison of appendectomy action through the antibiotic therapy administration in acute appendicitis patients - Shelvy Yuliavita; Ivy Fu Nakamura; Eirene Priscilla Caroline Simatupang; Michelle Sardjono; Nicolas Nurjadi (Institute of Computer Science (IOCS), 2023)
The purpose of this research to compare the effectiveness of appendectomy by administering non-operative management in the form of antibiotics in acute appendicitis patients. The research method used descriptive qualitative through the Literature Review (LR) approach. The data source used a secondary source. Data analysis technique selects literature based on title, year, and indexed articles, then reviews articles that match the subject matter. the articles from those journals are compared to find the differences and similarities. A literature review of four PubMed, DOAJ, Cochrane, and Google Scholar databases published in the last five years, i.e. from 2018-2022. Twelve pieces of literature were obtained and reported the advantages and disadvantages of each procedure. Apshortextomy keeps the gold standard with a lower risk of recurrence and severity and a higher treatment success rate. Appendectomy is also required for appendicitis cases with complications. However, antibiotic therapy has advantages with lower levels of complications, fewer costs, and fewer hospital stays. The success rate of non-operative therapy in the form of antibiotics can reach 65-75%, while it can reach 67,1% in children. There are differences in research results related to the effectiveness of appendectomy and antibiotic therapy in acute appendicitis patients. Each of these therapeutic procedures has its advantages and disadvantages. It is very important to be concerned about the urgency and expectations of the patient in selecting this therapy.